2020
DOI: 10.1158/2159-8290.cd-19-0837
|View full text |Cite
|
Sign up to set email alerts
|

TBK1 Is a Synthetic Lethal Target in Cancer with VHL Loss

Abstract: TANK binding kinase 1 (TBK1) is an important kinase involved in the innate immune response. Here we discover that TBK1 is hyperactivated by von Hippel-Lindau (VHL) loss or hypoxia in cancer cells. Tumors from patients with kidney cancer with VHL loss display elevated TBK1 phosphorylation. Loss of TBK1 via genetic ablation, pharmacologic inhibition, or a new cereblon-based proteolysis targeting chimera specifically inhibits VHL-deficient kidney cancer cell growth, while leaving VHL wild-type cells intact. TBK1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 55 publications
5
53
0
Order By: Relevance
“…Therefore, the up-regulated TBK1 expression, which is predictive of poor prognosis, may contribute to tumor progression especially in BRCA, KIRC, and LIHC. Consistent with our results, other studies reported that ectopic TBK1 expression accelerated the growth of BRCA by phosphorylating estrogen receptor α ( 13 ), and hyperactivated TBK1 was essential for maintaining p62 stability and the oncogenic phenotype of KIRC ( 47 ). However, there is limited knowledge regarding the effect of TBK1 on HCC progression.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the up-regulated TBK1 expression, which is predictive of poor prognosis, may contribute to tumor progression especially in BRCA, KIRC, and LIHC. Consistent with our results, other studies reported that ectopic TBK1 expression accelerated the growth of BRCA by phosphorylating estrogen receptor α ( 13 ), and hyperactivated TBK1 was essential for maintaining p62 stability and the oncogenic phenotype of KIRC ( 47 ). However, there is limited knowledge regarding the effect of TBK1 on HCC progression.…”
Section: Discussionsupporting
confidence: 92%
“…Six-week old female NOD SCID Gamma mice (NSG, Jackson Laboratory) were used for xenograft study. Approximately 5 × 10 5 viable 786-O cells were resuspended in 20 μL fresh growth medium and injected orthotopically into the left kidney of each mouse as described previously (24,25). Bioluminescence imaging was performed as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…Current research has gravitated toward identifying synthetic lethality targets to overcome therapy-resistance and impair cancer growth. We recently identified TBK1 as a synthetic lethal target in VHL-deficient kidney cancer [ 231 ], and inhibitors of TBK1 such as BX795, CYT387 481 (momelotinib), and MRT67307 can boost the efficacy of immune checkpoint inhibitors [ 232 ]. In addition, the use of veliparib, a drug that targets PARP-1, in combination with RAD51 deficiency, resensitizes hypoxic tumor colon carcinoma cells to radiation [ 233 ].…”
Section: From Mechanisms To Therapeuticsmentioning
confidence: 99%